2003
DOI: 10.1063/1.1589581
|View full text |Cite
|
Sign up to set email alerts
|

Semiclassical Monte Carlo model for in-plane transport of spin-polarized electrons in III–V heterostructures

Abstract: We study the in-plane transport of spin-polarized electrons in III-V semiconductor quantum wells. The spin dynamics is controlled by the spin-orbit interaction, which arises via the Dresselhaus (bulk asymmetry) and Rashba (well asymmetry) mechanisms. This interaction, owing to its momentum dependence, causes rotation of the spin polarization vector, and also produces effective spin dephasing. The density matrix approach is used to describe the evolution of the electron spin polarization, while the spatial moti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
77
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(79 citation statements)
references
References 74 publications
2
77
0
Order By: Relevance
“…Transient dynamics of spin drift and diffusion was considered by Fabian and Das Sarma (2002). Recently an interesting study (Saikin et al, 2003) was reported on a Monte Carlo simulation of quantummechanical spin dynamics limited by spin relaxation, in which quasiclassical orbital transport was carried out for the in-plane transport in III-V heterostructures where spin precession is due to bulk and structure inversion asymmetry (see Sec. III.B.2).…”
Section: Spin-polarized Drift and Diffusionmentioning
confidence: 99%
“…Transient dynamics of spin drift and diffusion was considered by Fabian and Das Sarma (2002). Recently an interesting study (Saikin et al, 2003) was reported on a Monte Carlo simulation of quantummechanical spin dynamics limited by spin relaxation, in which quasiclassical orbital transport was carried out for the in-plane transport in III-V heterostructures where spin precession is due to bulk and structure inversion asymmetry (see Sec. III.B.2).…”
Section: Spin-polarized Drift and Diffusionmentioning
confidence: 99%
“…A comprehensive review of the Monte Carlo method and its extension to inclusion of spin degree of freedom has been presented elsewhere 7,8,13 . We restrict our discussion to enlisting the essential features of our model.…”
Section: Modelmentioning
confidence: 99%
“…The electron-electron scattering merely leads to a redistribution in k space which is not of such a high importance in most conventional electronic systems. This tradition of not including electron-electron scattering has been carried over in one of the early works on Monte Carlo method for spin transport 13 , and in several subsequent works [14][15][16] . Given the nature of DP and EY spin relaxation mechanisms, electron-electron scattering is bound to be of utter importance.…”
Section: Introductionmentioning
confidence: 99%
“…Even without a source of spin injection, a nonequilibrium spin could be generated through the process of spin extraction [20,29] into a neighboring magnetic region. Our findings should also provide useful test cases for developing more general numerical methods for treating spin-polarized transport [30].…”
mentioning
confidence: 99%